WebObjects developer's guide - Mendis, Ravi (Kaleidoscope Ser., 2002)
WebObjects is an object-oriented Web application server that is used to generate scalable Web and Java applications from reusable templates. A product of Apple Computer, WebObjects¿ client list includes such Fortune 500 companies as Disney, Adobe, and the BBC. The product¿s support for Java 2 Enterprise Edition and its competitive pricing are expected to expand WebObjects¿ growing position in the market for Web application servers, a market that is expected to grow by more than $2 billion in revenue by 2002 (Forrester Research). WebObjects Developer¿s Guide is a unique, step-by-step guide for intermediate- to advanced-level developers. It uses a hands-on instructional approach to make the sophisticated and sometimes complex WebObjects technology accessible to developers. The book explains WebObjects concepts and paradigms, and it illustrates the art of modeling applications with the Enterprise Object Framework. The author provides practical insight into WebObjects development based upon his extensive experience as a consultant for major international corporations.